ANALISIS DAN PERANCANGAN SISTEM INFORMASI DALAM PEMBAYARAN ADMINISTRASI KEUANGAN SISWA DI SMA NOMMENSEN JAMBI - Lamtiur, Hosianna; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2019)
Nommensen High School is one of the Educational Institutions in Jambi City having its address at JalanBarau - Barau I Kel. Pakuan Baru Kec. South Jambi which was founded in 1988, which has a number of195 students with increasing numbers during the Nommensen High School in Jambi City experienced adevelopment. This development requires the existence of a means to accelerate performance andefficiency in School Administration especially School Financial Administration such as new studentregistration payment of tuition fees and committee fees, school financial expenditures and so ontherefore there is a need for a school financial administration management information system that canrecord, process and produce a fast school financial information system. In this system research systemdesign is used using UML mo deling which produces use case diagrams, activity diagrams and classdiagrams. The results of this study were in the form of a prototype. The purpose of this study is expectedto facilitate the management of school financial administration to be faster, more precise and accurate.